COMPARISON OF CLINICAL PROFILE AND OUTCOME OF MI IN SMOKERS AND NON-SMOKERS - Sumera Batool; Ashok Kumar; Nida Hussain; Wasfa Farooq; Muhammad Hamza Syed; Muhammad Hamza Syed; Nadeem Rizvi6 (ziauddin University, 2024)
ABSTRACT   Background: Myocardial infarction remains a leading cause of global morbidity and mortality. One major risk factor for atherosclerosis and MI is smoking, a highly prevalent habit in South Asian adolescents and healthcare professionals; particularly in Pakistan. This study was conducted to compare clinical presentation and outcome of myocardial infarction (MI) in smokers and non-smokers.   Methodology: This study included a total of 100 patients who presented to a tertiary care centre for cardiac patients in Karachi. Patients between 18-65 years presenting with MI were included in the study (N=100). They were divided into two groups, based on smoking status. The smoking group included patients who had smoked for 10 years or more. Patients who had smoked for less than 10 years or had quit less than 5 years back were excluded from both samples. Informed consent was taken from each participant.   Results: This study observed that 46% of the non-smokers as compared to 8% smokers present with chest pain (p = 0.001). Arrhythmia was seen in 20% of the smokers compared to 4% of the non-smokers (p = 0.001). Acute heart failure was seen in 24% smokers and only 4% non-smokers (p = 0.004). Of the smoking group, 32% of the patients expired despite treatment as compared to 6% of smokers (p = 0.001). Conclusions: Specific symptoms of myocardial infarction are more commonly seen in non-smokers, aiding early diagnosis and consequently leading to a good prognosis. Alternatively, fatal complications and death rate is a more likely outcome in smokers.